Precision medicine and phenotypes, endotypes, genotypes, regiotypes, and theratypes of allergic diseases - Agache, Ioana; Akdis, Cezmi A. (The Journal of clinical investigation, 2019)
A rapidly developing paradigm for modern health care is a proactive and individualized response to patients' symptoms, combining precision diagnosis and personalized treatment. Precision medicine is becoming an overarching medical discipline that will require a better understanding of biomarkers, phenotypes, endotypes, genotypes, regiotypes, and theratypes of diseases. The 100-year-old personalized allergen-specific management of allergic diseases has particularly contributed to early awareness in precision medicine. Polyomics, big data, and systems biology have demonstrated a profound complexity and dynamic variability in allergic disease between individuals, as well as between regions. Escalating health care costs together with questionable efficacy of the current management of allergic diseases facilitated the emergence of the endotype-driven approach. We describe here a precision medicine approach that stratifies patients based on disease mechanisms to optimize management of allergic diseases.